A novel method to identify and grade DNA damage on comet images. (August 2017) - Turan, Muhammed Kamil; Sehirli, Eftal
Abstract: Background and objective: In recent years, development of software programs in medicine field has proceeded in a rapid manner. Comet assay is one of the research methods in medicine field that displays whether DNA has damage. In this study, it is aimed to share experience of dynamic time warping method and decision tree to decide whether DNA has damage and grade DNA damage by means of the software program. Methods: The application analyzes manually extracted RGB single comet images whose centers are manually marked. The application performs pixel profile analysis at the directions of vertical and horizontal based on the center of comet. The bidirectional pixel profile results are used as inputs of dynamic time warping. Four novel and one conventional measurement parameters some of which are calculated by dynamic time warping are given to decision tree. Results: The decision tree identifies whether DNA has damage and grades DNA damage categorizing four damage levels with accuracy of 99.03% using only two of five measurement parameters. Conclusions: This paper mainly focuses on features and usage of dynamic time warping and decision tree as a novel method to identify and grade DNA damage on comet images.